Acute Kidney Injury in Pediatric Treated with Vancomycin and Piperacillin-Tazobactam in Tertiary Care Hospital - Mohammed Al Nuhait; Laila C. Abu Esba; Khalid Al Harbi; Meshary Al Meshary; Rami T. Bustami (International Journal of Pediatrics)
Background. Vancomycin and piperacillin-tazobactam (PTZ) are commonly used as empirical therapy for patients with health care associated infections. Vancomycin has been recognized as a nephrotoxic agent and in a few cases in the literature PTZ has been associated with interstitial nephritis nevertheless; the combination of these agents has routinely been used for many years. However, there have been some observational studies that showed high rates of acute kidney injury (AKI) in patients receiving vancomycin and PTZ concomitant treatment compared to patients receiving vancomycin alone. The incidence of AKI in adult patients receiving vancomycin and PTZ concomitant treatment was reported in these studies to be relatively high. Similar studies in pediatric patients are lacking. Method. We conducted a single center retrospective chart review of 248 pediatric patients receiving one of the following treatments: vancomycin alone 36 patients, vancomycin/PTZ 62 patients, vancomycin/ceftazidime 99 patients, and vancomycin/ceftriaxone 51 patients. Result. Our results showed a low incidence of AKI in patients on vancomycin/PTZ concomitant treatment where overall incidence was only (4.8%) three cases and only one of them (2.0%) in a patient receiving the vancomycin/ceftriaxone concomitant treatment. No cases of AKI present in patients receiving vancomycin with ceftazidime or vancomycin alone. There were no statistically significant differences between the four treatment groups in terms of AKI incidence, vancomycin trough, and use of nephrotoxins. Conclusion. Overall, the incidence of AKI was low in our study sample with no statistically significant increased risk when PTZ was used in combination with vancomycin in a pediatric population. However, further investigation with an equal larger sample size is needed to confirm our findings.